Тексти про Т. Шевченка й Шевченкові тексти в практиці навчання української мови іноземців - Швець, Ганна; Shvets, Anna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано шевченківську тематику в сучасній текстотеці з української мови як іноземної. З’ясовано, що ефективне використання текстів про Т. Шевченка в навчальному процесі можливе за умови комунікативно-діяльнісного підходу. Обґрунтовано обмежене використання Шевченкових творів у навчанні іноземців різних спеціальностей і схарактеризовано специфіку ознайомлення іноземних філологів із поезіями митця.The article analyzes texts about T. Shevchenko and Shevchenko’s texts in the modern training text material on Ukrainian as a foreign language. It determines that the effective using of texts about T. Shevchenko and other cultural texts in the educational process perhaps with communicative-active approach in language teaching. It explains the limited using of Shevchenko’s texts in work with foreign students of different specialties, especially in the beginning. The author identifies some of the poet’s works that can be recommended for students of the preparatory faculty while working on the lexical theme «The Family». The article outlines the specifics of familiarization of foreign philologists with the poet’s creativity, the ways of overcoming the gap between the level of development of their reading competency and complexity of Shevchenko’s works.
Texts About T. Shevchenko and Shevchenko s Texts in the Practice of Teaching Ukrainian to Foreigners.
Keywords: текст; навчальний текст; комунікативна компетентність; читацька компетентність; комунікативно-діяльнісний підхід; text; educational text; communicative competence; reader’s competence; communicative and active approach; Ukrainian as a foreign language